Multifunctional polymeric wound dressings - Soylu, Zelal; Oktay, Buesra; Erarslan, Azime; Ozerol, Esma Ahlatcioglu (SPRINGER, 2025)
Wound healing is a multifaceted process influenced by various biological and mechanical factors, necessitating personalized treatment approaches. Wound dressings have become a crucial component of wound care due to their non-invasive nature and ability to create a controlled healing environment. However, traditional dressings often lack the mechanical strength and bioactivity required for optimal healing, driving research into biomaterials and advanced fabrication techniques to enhance their functionality. Recent advancements have culminated in the development of biofunctional wound dressings that exhibit high biocompatibility, non-toxicity, and the ability to accelerate the healing process while maintaining mechanical integrity suitable for different wound types. These next-generation dressings incorporate protective barriers, absorb wound exudates, and provide antimicrobial, anti-inflammatory, and tissue-regenerating properties. The integration of multifunctional and smart wound dressings with nanofibrous scaffolds, platelet-rich fibrin, and 3D-printed biomaterials has enhanced their therapeutic efficiency by mimicking the natural extracellular matrix and enabling controlled drug delivery. Additionally, sensor-integrated dressings capable of real-time wound monitoring and stimulus-responsive drug release represent a promising avenue for personalized wound care management. This review provides a comprehensive analysis of modern wound dressing technologies, their classification, and the biomaterials utilized in their fabrication. It also highlights the advantages of biofunctional and smart dressings in promoting efficient wound healing and tissue regeneration.
Keywords: Wound dressing; Wound healing; Multifunctional; Smart; Biopolymer; Nanofibrous scaffold; Platelet-rich fibrin; 3D-printed biomaterials; IN-VITRO; ANTIBACTERIAL ACTIVITY; NANOFIBERS; ACID; EXTRACT; HYDROGELS; OIL; PH; ANTIOXIDANT; MEMBRANES; Polymer Science